P242 Accuracy of Doppler transabdominal ultrasound in assessing disease severity and extent in IBD. (25th January 2019) - Sagami, S; Kobayashi, T; Kanazawa, T; Aihara, K; Morikubo, H; Ozaki, R; Okabayashi, S; Matsubayashi, M; Fuchigami, A; Kiyohara, H; Nakano, M; Hibi, T
Abstract: Background: A paradigm shift in the treatment of inflammatory bowel disease (IBD) has emerged with recent medical advancements. Beyond clinical remission, endoscopic mucosal healing has become a major therapeutic goal of IBD and is associated with better long-term prognosis. Therefore, endoscopic evaluation is considered indispensable, however, frequent ileocolonoscopy (CS) may not be feasible due to its invasiveness. Transabdominal ultrasonography (TAUS) is a non-invasive imaging technique which enables to frequently monitor the disease and its utility has been previously reported. This study examined the usefulness of Doppler TAUS in assessing disease severity of IBD comparing with CS for each ileocolonic segment. Methods: A retrospective chart review of 60 patients with IBD (ulcerative colitis (UC) 35, Crohn's disease (CD) 25) who were examined both CS and Doppler TAUS from May 2017 to November 2018 within the interval of 1 month was conducted. The Mayo Endoscopic Subscore (MES) or the Simple Endoscopic Score for Crohn's disease (SES-CD) were used for CS and Limberg score was graded from Grade 0 to 4 for Doppler TAUS [2] . Endoscopic scoring indices (MES, SES-CD) and Limberg score were compared per-segment (ileum, ascending, transverse, descending, sigmoid and rectum) and per-patient. The sum of each score was calculated. Finally, the association of Limberg score with endoscopic indices was assessed by non-parametric Spearman rank correlation ( r s ) and receiver-operating characteristic analysis. Results: Limberg score was significantly associated with MES (rs = 0.68, p < 0.01) or SES-CD in per-patients analysis ( r s = 0.53, p < 0.01). The sum of Limberg scores of five segments also well-correlated with the sum of MES ( r s = 0.84, p < 0.01) and SES-CD ( r s = 0.76, p < 0.01). Per-segment analysis (UC: 208 segments, CD: 149 segments) demonstrated a significant correlation between Limberg score and MES/SES-CD ( r s = 0.84 and 0.67, respectively). Association was significant in ileum, ascending, transverse, descending, and sigmoid colon, whereas not significant in rectum (Table 1). Limberg score ≤1 had a sensitivity of 1.00 and a specificity of 0.75 for mucosal healing defined by MES ≤ 1 or SES-CD (ulcer score) = 0 with area under the receiver-operating characteristic curve values of 0.91. Conclusions: Doppler TAUS is a useful monitoring tool alternative to CS, however, is less accurate in the assessment of rectum. References 1. Sturm A, Maaser C, Calabrese E, et al. ECCO-ESGAR guideline for diagnostic assessment in inflammatory bowel disease. J Crohns Colitis 2018. doi:10.1093/ecco-jcc/jjy114. 2. Limberg B. Diagnosis of chronic inflammatory bowel diseases by ultrasonography. Z Gastroenterol 1999;37:495–508.